Strategies Used to by Mothers with Breast Cancer to Apply the Mothering Role: A Qualitative Study - Vahid Zamanzadeh; Akram Ghahramanian; Leila Valizadeh; Effat Mazaheri (Hamadan University of Medical Sciences, 2021)
Background and Objective: Women with breast cancer often experience alterations in their mothering roles both because of the disease and the reduced ability for child care. However, many women with breast cancer try to play their mothering roles as they did before the disease. This study aimed to discover the strategies used by Iranian women with breast cancer to manage their mothering roles in the process of the disease and survival. Material and Methods: A qualitative content analysis study was conducted on 23 mothers with breast cancer. Semi-structured interviews were used to collect data and a conventional content analysis method was used to analyze the data simultaneously with data collection. Results: Totally 1200 non-duplicate codes were extracted from the data and were categorized into four categories. Self-preparation was the first category and included three subcategories, namely, self-awareness for regaining the role, psychological mobilization to continue the role, and seeking informational support. Role reorganizing was the second category and had two subcategories, namely assigning to alternate people, and modifications of maternal duties. Self- and family-reconstruction was the third category and included three subcategories of energy conservation, communication development, and child protection. Playing a participatory-supervisory role was the fourth category and had two subcategories of participation and supervision. Conclusion: Identifying the strategies used to play the mothering role can help health care professionals to support, provide advice, and train the mothers with breast cancer and their families. It also helps mothers to play their mothering role during the disease.